ALKALINE PHOSPHATASE: SIGNIFICANCE IN DAIRY INDUSTRY - Darshana Prajapatia, Kalpna Desai. S.N. Patil, S.V. Chaudhari (International Journal of Research Science and Management, 2017)
Alkaline phosphatases (ALP, EC 3.1.3.1) is widely present in nature, and are found in many organisms. Alkaline phosphatase is an enzyme which catalyzes the hydrolysis of phosphate monoesters. ALP is located on the luminal surface of the epithelial cells of the ducts, it is released into milk as part of the plasma membrane during the formation of milk fat globules.